2022
DOI: 10.1371/journal.pone.0274718
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement to increase vaccine uptake: Quasi-experimental evidence from Islamabad and Rawalpindi, Pakistan

Abstract: Developing countries have been facing difficulties in reaching out to low-income and underserved communities for COVID-19 vaccination coverage. The rapidity of vaccine development caused a mistrust among certain subgroups of the population, and hence innovative approaches were taken to reach out to such populations. Using a sample of 1760 respondents in five low-income, informal localities of Islamabad and Rawalpindi, Pakistan, we evaluated a set of interventions involving community engagement by addressing de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Infodemic management, risk communication and continued vaccine education to clear safety concerns are, thus, warranted. Moreover, considering flexible vaccination options such as mobile vaccination units where people can be vaccinated at their homes or workplace would solve access barriers faced among slum and underserved communities [ 46 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infodemic management, risk communication and continued vaccine education to clear safety concerns are, thus, warranted. Moreover, considering flexible vaccination options such as mobile vaccination units where people can be vaccinated at their homes or workplace would solve access barriers faced among slum and underserved communities [ 46 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community engagement was identified as an important enabler to COVID‐19 vaccination programs which mirrored other international studies 32–36 . Tjilos et al, 34 a qualitative study of community‐engaged conversations about COVID‐19 vaccinations in New England, USA, found that community leaders suggested utilising existing social networks and trusted community leaders to disseminate credible information.…”
Section: Discussionmentioning
confidence: 60%
“…Community engagement was identified as an important enabler to COVID-19 vaccination programs which mirrored other international studies. [32][33][34][35][36] Tjilos et al, 34 a qualitative study of community-engaged conversations about COVID-19 vaccinations in New England, USA, found that community leaders suggested utilising existing social networks and trusted community leaders to disseminate credible information. This is particularly important in rural areas where such engagement plays an important role in public health responses 23 and can be utilised to ensure that programs are targeted to specific community needs rather than using a 'one size fits all' approach that often excludes marginalised groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization’s technical advisory group on behavioral insights and sciences for the health [ 46 ], community engagement can be beneficial in pre-designing vaccination methods and messaging, sharing timely information about vaccine strategies, fostering trust, and addressing false information. For example, community engagement was essential to increase COVID-19 vaccination awareness and uptake in small communities in Pakistan [ 47 ]. In addition, researchers leveraged community leaders to improve vaccine willingness by changing residents’ behavioral intentions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, community engagement was essential to increase COVID-19 vaccination awareness and uptake in small communities in Pakistan [ 47 ]. In addition, researchers leveraged community leaders to improve vaccine willingness by changing residents’ behavioral intentions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%